2021
DOI: 10.1016/j.biopsych.2021.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Behavioral Phenotypes in a Mouse Model of DDX3X Syndrome

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The former class likely results in DDX3X haploinsufficiency and/or hypomorphic loss-of-function (LoF) ( Figure 1A ). Consistent with this, in female mice, Ddx3x germline haploinsufficiency impairs postnatal brain architecture and causes behavioral deficits phenocopying aspects of human DDX3X syndrome ( Boitnott et al, 2021 ). In addition, using transient CRISPR approaches we previously showed that acute Ddx3x depletion in a subset of cells perturbed progenitor and neuron number ( Lennox et al, 2020 ).…”
Section: Introductionmentioning
confidence: 58%
“…The former class likely results in DDX3X haploinsufficiency and/or hypomorphic loss-of-function (LoF) ( Figure 1A ). Consistent with this, in female mice, Ddx3x germline haploinsufficiency impairs postnatal brain architecture and causes behavioral deficits phenocopying aspects of human DDX3X syndrome ( Boitnott et al, 2021 ). In addition, using transient CRISPR approaches we previously showed that acute Ddx3x depletion in a subset of cells perturbed progenitor and neuron number ( Lennox et al, 2020 ).…”
Section: Introductionmentioning
confidence: 58%
“…1A). Consistent with this, in female mice, Ddx3x germline haploinsufficiency impairs postnatal brain architecture and causes behavioral deficits phenocopying aspects of human DDX3X syndrome (Boitnott et al 2021). In addition, using transient CRISPR approaches we previously showed that acute Ddx3x depletion in a subset of cells perturbed progenitor and neuron number (Lennox et al 2020).…”
Section: Introductionmentioning
confidence: 62%
“…New insights into Ddx3x dosage requirements and redundant roles of DDX3X and DDX3Y would not have been gained with germline LoF models, due to male lethality (Chen et al 2016a). A recent report assessed behavioral phenotypes of a germline mouse model of Ddx3x haploinsufficiency in females (Boitnott et al 2021). Consistent with our cHet phenotypes, these females were not microcephalic, but did have reduced Ctip2+ (layer V) neurons in the somatosensory cortex at P3, which persisted into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Dd3x neural stem cells knockout at embryonic day (E) 9.5 in mice hampered brain growth, accompanied by seizures and ataxia ( Patmore et al, 2020 ). Boitnott et al (2021) generated a Ddx3x haploinsufficient mouse (Ddx3x ± female) with construct validity for DDX3X loss-of-function mutations. The Ddx3x ± mice showed global development delay and evolved into behavioral anomalies in adulthood ( Boitnott et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Boitnott et al (2021) generated a Ddx3x haploinsufficient mouse (Ddx3x ± female) with construct validity for DDX3X loss-of-function mutations. The Ddx3x ± mice showed global development delay and evolved into behavioral anomalies in adulthood ( Boitnott et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%